Times and Sizes of Jumps in the Mexican Interest Rate - José Antonio Núñez Mora; Arturo Lorenzo Valdés (Análisis Económico, 2008)
This paper examines the role of jumps in a continuous-time short-term interest rate model for Mexico. A filtering algorithm provides estimates of jumps times and sizes in the time series of Mexican cetes for the 1998-2006 period. The empirical results indicate that the inclusion of jumps in the diffusion model represents a better alternative than not to include them.